Gula Melaka Asli Hj Shaari / Asyraf Che Mohamad Nor … [et al.] - Che Mohamad Nor, Asyraf; Ahmad, Hafsah; Isderis, Dania Arisya; Wan Mohd Azana, Wan Muhammad Hazim; Ya’akob, Muhammad Yusuf (2022)
Gula Melaka Haji Shaari is a sole proprietor business founded by Haji Shaari Bin Adam aged 72 years old. He started his own business in 1995 when he was 16 years old. Gula Melaka Haji Shaari is a home-based business and it is originally from Kampung Serkam, Merlimau Melaka. Gula Melaka Haji Shaari is a business that produces Gula Melaka. Haji Shaari got the idea to sell Gula Melaka when there were a few leased coconut trees and that is when he started making Gula Melaka. The business name is originally from his own name which is ‘ Shaari Bin Adam. This is because he wants to differentiate with other Gula Melaka sellers that already exist in the market. His aim at first was to sell to the kuih's seller but now he also focused on selling Gula Melaka to the restaurant owner. Not as before when he only promoted his products by sending it through the small shops, now Gula Melaka Haji Shaari using social media platforms such as Whatsapp to promote his product more widely than before. His product is unique compared to the others' same product because he is the only distributor and manufacturer that produces the ‘Original’ Gula Melaka in Melaka. Gula Melaka Asli Haji Shaari have strengths that made the business become successful. This is because Gula Melaka is already known by people whether in Melaka or outside of Melaka. So it is easy to promote and they already know the use of Gula Melaka itself. Other than that, Gula Melaka Asli Haji Shaari produces the only Original Gula Melaka that is from Coconut tree and no preservative added in the products. Gula Melaka Asli Haji Shaari also already has loyal customers that always order and buy Gula Melaka Asli from him. But in business, it also has weaknesses that we should take action on, the same as Haji Shaari’s business. In his business, the Gula Melaka Asli that he produces is easily melted because there are no preservatives added in the product. Other than that, the product also cannot stand the heat. Gula Melaka Asli Haji Shaari has less customers through online mediums. These three weaknesses should he take action and focus more on how to fix it to make the business become more successful. Gula Melaka Haji Shaari’s price strategies are based on the product's sizes, cost, customers and competitors. Haji Shaari takes care of his customers by always checking on product quality and being honest in the business.